Cryoconite on a glacier on the north-eastern Tibetan plateau: light-absorbing impurities, albedo and enhanced melting. Issue 252 (24th June 2019) - LI, YANG; KANG, SHICHANG; YAN, FANGPING; CHEN, JIZU; WANG, KUN; PAUDYAL, RUKUMESH; LIU, JINGSHI; QIN, XIANG; SILLANPÄÄ, MIKA
ABSTRACT: Cryoconite is a dark-coloured granular sediment that contains biological and mineralogical components, and it plays a pivotal role in geochemistry, carbon cycling and glacier mass balance. In this work, we collected cryoconite samples from Laohugou Glacier No. 12 (LHG) on the north-eastern Tibetan Plateau during the summer of 2015 and measured the spectral albedo. To explore the impacts of this sediment on surface ablation, the ice melting differences between the cryoconite-free (removed) ice and the intact layers were compared. The results showed that the mean concentrations of black carbon (BC), organic carbon (OC) and total iron (Fe) in the LHG cryoconite were 1.28, 11.18 and 39.94 mg g −1, respectively. BC was found to play a stronger role in solar light adsorption than OC and free Fe. In addition, ice covered by cryoconite exhibited the lowest mean reflectance (i.e., <0.1). Compared with the cryoconite-free ice surface, cryoconite effectively absorbed solar energy and enhanced glacial melting at a rate of 2.27–3.28 cm d −1, and free Fe, BC and OC were estimated to contribute 1.01, 0.99 and 0.76 cm d −1, respectively. This study provides important insights for understanding the role of cryoconite in the glacier mass balance of the northern Tibetan Plateau.